Karakteristik sifat fisik dan pH tanah pada kebun percobaan Anggori Universitas Papua - Paulince Yarangga; Samsul Bachri; Kati Syamsudin Kadang Tola; Rudolf Kristian Tukayo (Fakultas Pertanian Universitas Papua, 2021)
This study aims to determine the characteristics of the physical properties and soil pH in the Anggori experimental garden belonging to the University of Papua. The Anggori experimental garden is one of the Unipa experimental gardens which has great potential as a means of supporting lecturers and students across faculties. Based on the results of the study, it was found that the color of the soil at the research site on the top and bottom layers tended to have the same color, which was dominated by dark brown and dark yellowish brown. The soil texture ranged from sandy loam, loamy loam, silty loam and clay loam, with soil structure which is granular, rounded lumps, and angular lumps, with medium to fine size, as well as moderate to weak stability. The consistency of the soil were rather sticky, loose, and weak. There were rocks on the surface and rock outcrops <25%, with good drainage. Effective depth of soil was >40 cm and soil acidity (pH) was classified as slightly acidic to neutral.